Integrated multi-omics analysis identifies TPX2 as a potential prognostic and immunological biomarker in hepatocellular carcinoma - Hui Peng; Yong-peng Wei; Xin-bo Liu; Yu Wang; Jian-yong Yuan (iLIVER)
Background and aims: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide, characterized by aggressive behavior, limited therapeutic efficacy, and poor patient outcomes. TPX2, a microtubule-associated protein essential for mitotic spindle formation, has been associated with tumorigenesis in various cancers. However, its functional significance in shaping the immune landscape and influencing treatment sensitivity in HCC remains insufficiently elucidated. Methods: We conducted an integrated multi-omics analysis using transcriptomic (TCGA, GTEx, GEO), proteomic (CPTAC), and pharmacogenomic (GDSC, PRISM, CTRP) datasets to assess TPX2 expression patterns in HCC. We performed differential expression analysis, survival analysis, Cox regression, and nomogram construction. Co-expression modules were identified via weighted gene co-expression network analysis (WGCNA), followed by GO and KEGG enrichment analyses. The correlations between TPX2 expression levels and immune and genomic features were examined, and drug sensitivity associations were evaluated. Results: TPX2 was consistently overexpressed in HCC tissues and associated with advanced tumor stage, higher grade, and poor survival. WGCNA revealed TPX2-enriched modules linked to cell cycle and DNA replication pathways. High TPX2 expression levels were correlated with immunosuppressive features, including reduced lymphocyte infiltration, lower IFN-γ response, and increased expression levels of immune checkpoint molecules (PD-1, CTLA-4, HAVCR2). TPX2-high tumors also exhibited greater genomic instability. Drug sensitivity analysis indicated resistance to several chemotherapeutics, but increased sensitivity to mitotic inhibitors and targeted agents. Conclusions: TPX2 is a key driver of proliferation and immune evasion in HCC, potentially serving as a diagnostic and prognostic biomarker to guide treatment strategies involving mitotic- or immune-based therapies.